A Gamified Drill Method: Systematic Development of Digital Educational Games for Arabic Reading Skills - Muhammad Farhan Brilliant; Syaiful Musthofa; Abdul Muntaqim Al Anshory (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The mastery of Arabic reading skills (Maharah Qira’ah) among students often faces significant challenges due to the monotony of traditional methods and the lack of interactive media. This research addresses the urgent need for pedagogical innovation by developing a digital educational game based on the Drill Method, designed to transform repetitive linguistic practice into an engaging experience. The study utilized the Research and Development (R&D) method, involving 23 tenth-grade students at SMA Muhammadiyah 1 Malang as the primary research subjects. The development process integrated iSpring Suite with Gemini AI-generated assets to ensure high-quality visual aesthetics and technical stability. Validation results from experts demonstrated exceptional feasibility, with the material expert providing a perfect score of 100% and the media expert scoring 97.92%. Implementation data revealed that the